From Carl Menger's theory of goods to an evolutionary approach to consumer behaviour - Wilhelm Ruprecht (Max Planck Institute of Economics, 2005)
A characteristic feature of economic development is the ever changing structure of consumption patterns. Reducing the explanation of this phenomenon to changing prices, finally caused by changes in the availability of goods (or characteristics), would neglect a major force driving this change, i.e. the variation of consumer wants and consumer knowledge. The present paper aims at sketching an evolutionary framework for the analysis of consumer behaviour that takes account of these features. For this purpose, Carl Menger's theory of goods is taken as a starting point. Whereas economists after the 'marginalistic revolution' were almost exclusively concerned with the determinants of exchange value and developing price theory, Menger puts as much emphasis on the user value as on the exchange value. Regarding the way of how user value changes a connection between Menger's 19th century theory of goods and 20th century learning theories is established. The problem of how to get from individual learning processes to aggregate consumption patterns is approached by recollecting the genetic underpinnings of human learning and its contingency on certain physical and social conditions. Taking into account that these conditions are dynamic, the presented approach allows interpreting collective learning processes as historical events and makes them fruitful for the analysis of economic change.
Keywords: A12; B25; B52; B53; D11; D83; 330; Austrian economics; evolutionary economics; consumer theory; learning; Konsumgut; Konsumtheorie; Konsumentenverhalten; Evolutionsökonomik